Systematic review and classification of: PMTO-Parent training in groups - Adolfsen, Frode; Reedtz, Charlotte; Koposov, Roman; Fossum, Sturla (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2022)
Background: This article sums up the effects of PMTO-Parent training in groups. The article is a revision of an earlier description of the same programme in Ungsinn but is developed according to new criterions and procedures. The intervention is based on the content from Parent Management Training the Oregon model (PMTO), but this intervention is a group treatment with up to 16 parents (eight couples) for a total of 12 sessions. The groups are led by two certified group leaders. The target group for the intervention is parents with children with initial behavioral problems or at risk of developing more severe conduct problems. Method: The databases used to identify studies of the intervention included Embase, Medline, Psychinfo, Cochrane, Cristin, Nora, Scopus and Svemed. Results: Three randomized controlled trials (RCT) evaluating the PMTO-Parent training in groups were identified and included. The first study consists mainly of Norwegian children and parents. The next one is an intervention with minority children and their mothers, and the last one is a RCT with foster parents. The intervention is well described and has a sound theoretical fundament. All the studies are evaluated to have satisfactory to good scientific quality. The effects of the intervention were mainly small to moderate, and the intervention has a god strategy for implementation and quality assurance. Conclusion: The studies evaluating the intervention had relatively good scientific quality, and resulted in small to moderate effects of the intervention. The main findings in the included studies indicate that child behavioral problems are reduced as a consequence of the intervention, and that parenting skills are being strengthened. The intervention is therefore expected to be useful for many children in the target group. The intervention is classified on evidence level 4 – as an intervention with satisfactory documentation of effect.